Determination of proper college student chair dimension and comparison with the prevalent model - Ali Byat kashkoli; Morteza Nazaryan (تحقیقات علوم چوب و کاغذ ایران, 2011)
Definition of furniture design and its products according to the principles of anthropometry is essential and meaningful. Dimensions of chair should optimize fitting based on anthropometric measurements of population. The research explores the appropriate chair dimension which best fit the anthropometric characteristics of Zabol students. The applied methodologies were descriptive and approximate. Anthropometric measurements of Zabol students, include back height, arm-shoulder to elbow, popliteal height, buttock popliteal height and hip circumference, and statistical analyzes, include Duncan analysis and descriptive statistics used and proper dimension of chair were determinate by the guideline.  A total of 140 students (15 female and 20 male representing each of the four bachelor duration) were sampled. Dimension of all chairs variety were recorded. Differences of anthropometric measurements of 60 people were measured to available education chair. The obtained results showed that the chair dimensions were greater than the acceptable limits for most students. If chair dimensions, include armrest height, seat height, seat depth, seat width and backrest height are equal to 20, 42, 38, upwards of 59 and 35 cm, match percent could be improved to 32%, also, 49%, 49%, upwards of 59% and 44%, respectively.